(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The constitution of India guaranteed to every woman constitutional morality, dignity of women and the principles of gender equality, as also against gender equity. It is the duty of legislation would help in ensuring the larger Constitutional goals of gender justice and gender equality of married Muslim women and help subserve their fundamental rights of non-discrimination and empowerment. However constitutional rights would remain a dead letter if we do not understand the manner in which identity politics unfolds especially in case of women. contemporary issue of triple talaq has become a battleground for the culture versus modernity debate.The issues dealt with by the Apex Court in reaching the verdict included, whether Triple Talaq was a matter of faith and thus protected under Article 14, 15, 2125 of the Constitution? Whether the Court of law can interpret religious scriptures of any religious denomination contrary to the interpretation put on it by the religious books and authorities, held authentic by such denomination? Does the practice of Triple Talaq forms the part of personal law? Did the Muslim Personal Law (Shariat) Application Act, 1937 (Shariat Act) confers statutory status to the subjects regulated by it? Whether Instant Triple Talaq was bad in theology and good in law?The first part of the paper shall analyze the Re Muslim Women’s Quest for Equality versus Jamiat Ulma-I-Hind[1] and Shayara Bano Vs. Union of India[2] petition and the argument put forward by the same. The second part of the paper shall deal with the alternative legal remedies available to the Muslim women in the current legal set-up. The author shall advocate that taking cue from third wave feminism, the identity of Muslim women must be understood at the intersection of gender and religion.